Novel Patient-Reported Outcome Measures for the Assessment of Patient Satisfaction and Health-Related Quality of Life Following Postmastectomy Breast Reconstruction - Tichá, Pavla; Wu, Meagan; Bujda, Michele; Sukop, Andrej (Aesthetic plastic surgery, 2022)
BACKGROUND: Patient-reported outcome measures (PROMs) have become an integral part of the evaluation of reconstruction surgery outcomes. However, there are limitations in current PROMs when it comes to the assessment of well-being during inpatient stay, patient perception of health, relationship with partner, and vitality (i.e., mood and ability to work and pursue hobbies, carry out daily tasks, and sleep) following breast reconstructive surgery. The aim was to develop a novel set of measures to compare patient satisfaction and health-related quality of life following different types of postmastectomy breast reconstruction. METHODS: A novel questionnaire was created and refined through cognitive interviews with patients and expert feedback. A field test study was conducted, including patients who had undergone delayed postmastectomy breast reconstruction with implant, autologous tissue, or combination of implant and autologous tissue. Based on the results, confirmatory factor analysis and examination of reliability of the questionnaire were conducted. Results of patient responses were analyzed using Chi-square test, Kruskal-Wallis test, and Mann-Whitney U test. RESULTS: Confirmatory factor analysis showed good model fit, and Cronbach's alpha indicated high internal consistency of the questionnaire. Besides that, patients with combination reconstruction reported significantly lower vitality than patients with implant and autologous reconstruction (p = 0.048). CONCLUSIONS: This novel questionnaire expands the current knowledge base of postmastectomy breast reconstruction PROMs. Results of the field test study showed that combination reconstruction was associated with lower patient vitality than other reconstruction types. LEVEL OF EVIDENCE IV: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .
Keywords: Patient Satisfaction; Treatment Outcome; Retrospective Studies; estetika; nádory prsu; lidé; Reproducibility of Results; Breast Neoplasms; Mammaplasty; reprodukovatelnost výsledků; Mastectomy; Female; výsledek terapie; Cohort Studies; kohortové studie; Esthetics; Patient Reported Outcome Measures; ženské pohlaví; mastektomie; kvalita života; Humans; Quality of Life; mamoplastika; spokojenost pacientů; hodnocení výsledků péče pacientem; retrospektivní studie